SYNTHESIS AND CHARACTERIZATION OF Cu (II) COMPLEXS WITH 1,4,8-TRIS(2-HIDROXYMETHIL)-11-METHYL-1,4,8,11-TETRAAZACYCLOTETRADECANE - Sentot Budi Rahardjo (Universitas Gadjah Mada, 2003)
Cu (II) complexs with 1,4,8-tris(2-hidroxymethyl)-11-methyl-1,4,8,11-tetraazacyclotetradecane (L) have been synthesized with chemical formula of [CuL](ClO4) (experimental Cu = 32.7 %, H = 6.4%, theoritical Cu = 32.6 %, H = 6.4 %). Its magnetic moment of 1.90 BM indicated that the complexs is paramagnetic and there are no Cu-Cu bonding. This complexs is stable with the value of log k [CuL]2+ = 17.3(2). Visible spectra of [CuL]2+ showed that single wide peak at λmax of 628 nm (ε = 164 dm3.mol-1.cm-1) and indicated of E9 - T29 transition. The IR spectra and the conductancy data indicated that the ClO4 was not coordinated to Cu.